Microfinance industry and its impact on society: A study in Yemen / Zakarya Ameen Mohammed Dammag - Zakarya Ameen , Mohammed Dammag (2019)
This study is related to the microfinance industry which is one of the most important economic topics for community development. Microfinance refers to the provision of financial services by certain financial institutions involving such as loans, savings, insurance and fund transfers to entrepreneurs, small businesses and individuals who lack access to traditional banking services. The study aims to measure the impact of microfinance on the Yemeni community benefiting from this funding in improving living standards in addition to highlighting the role of microfinance in creating new job opportunities and reducing unemployment in Yemen. In addition, this study aims to explore the contribution of microfinance programs to the sustainability of small-funded firms and investigate the impact of micro-financing distribution. Refers to previous studies, this study explains the theoretical concept of small and micro enterprises as well as the microfinance industry. To achieve the research objectives, this study applies quantitative methods involving a random sampling of 449 microfinance program beneficiaries who receive funding among the Yemeni community for the period 2009 to 2016. This study found that the four hypotheses stated at the beginning of the study were supported. Analysis shows that microfinance has a positive impact on beneficiaries during the review period. Furthermore, the study has several conclusions as follows: First, the Yemeni government has proven to be of great importance to the microfinance industry through the enactment of specialized laws on microfinance. Secondly, the microfinance industry has proven to have contributed to improving the standard of living of the Yemeni community. Thirdly, microfinance beneficiaries were not only able to obtain employment in the private sector, but also, they participated in the economy development of the country. Additionally, the study found that microfinance has contributed to the increased capital of the financed projects. Moreover, the empirical findings revealed that microfinance beneficiaries had no difficulty in obtaining the funding and had not faced problems related to the procedures for obtaining such financing. Based on the findings and findings, this study has presented some basic implications or suggestions that can help improve the research and development of microfinance in Yemen.